1996
DOI: 10.1002/elps.1150170223
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic separation of recombinant tissue‐type plasminogen activator glycoforms: Validation issues for capillary isoelectric focusing methods

Abstract: Attempts were made to validate a capillary isoelectric focusing (cIEF) method for a recombinant glycoprotein as an alternative technique to slab gel isoelectric focusing methods routinely used to monitor such charge heterogeneity. The cIEF method principally separates the charged glycoforms of recombinant tissue-type plasminogen activator (rt-PA) on the basis of their sialic acid content. Nine to ten distinct peaks were consistently resolved, with the profile dependent on the class of ampholyte used. The pI of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…In addition, CE provides product information orthogonal to HPLC [40,50]. To date, validation of CE separations of (recombinant) proteins is mainly focused on CZE and CGE-SDS [38,[51][52][53][54], whereas CIEF validation is scarcely reported [41,45,55,56]. Despite the availability of several CE separations for the characterization of (recombinant) allergens [57][58][59][60][61][62][63], only a single validated CZE method has been published so far [57].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, CE provides product information orthogonal to HPLC [40,50]. To date, validation of CE separations of (recombinant) proteins is mainly focused on CZE and CGE-SDS [38,[51][52][53][54], whereas CIEF validation is scarcely reported [41,45,55,56]. Despite the availability of several CE separations for the characterization of (recombinant) allergens [57][58][59][60][61][62][63], only a single validated CZE method has been published so far [57].…”
Section: Introductionmentioning
confidence: 99%
“…Protein recovery from the coated capillary was observed to be > 90%, the limit of detection was determined, and the precision of the area percent shown to be acceptable. However, due to the variability of residual EOF in different lots of the coated capillary, resulting in highly variable migration patterns and migration times, these capillaries were deemed unacceptable [55]. Hunt el al.…”
Section: Reviews Of Ce Used For the Analysis Of Recombinant Proteinsmentioning
confidence: 99%
“…Therefore, these methods could be used to determine concentration (strength) of the active component in the final dosage form. The validation of a one-step clEF method for demon stating consistency of rt-PA glycoforms was attempted by Moorhouse et al [55]. Protein recovery from the coated capillary was observed to be > 90%, the limit of detection was determined, and the precision of the area percent shown to be acceptable.…”
Section: Reviews Of Ce Used For the Analysis Of Recombinant Proteinsmentioning
confidence: 99%
“…In addition to zone electrophoretic methods, Cifuentes et al [99] have reported the analysis by cIEF of rEPO: all the isoforms were resolved in the pH 2.5-5.0 interval. Isoelectric focusing techniques were also used for studying the heterogeneity of tissue plasminogen activator, as reported by Thorne et al [100] and by Moorhouse et al [101].…”
Section: Ce Analysis Of Proteinsmentioning
confidence: 99%